2003
DOI: 10.1093/jxb/erg244
|View full text |Cite
|
Sign up to set email alerts
|

Heat-stress-dependency and developmental modulation of gene expression: the potential of house-keeping genes as internal standards in mRNA expression profiling using real-time RT-PCR

Abstract: The potential of different house-keeping genes for their use as internal standards of gene expression under changing environmental conditions and in different organs of plants was assessed. Using real-time PCR mRNA levels were precisely quantified for preselected actin and ribosomal protein genes in Arabidopsis thaliana (L.) Heinh. and Nicotiana tabacum L. grown at normal temperature and following heat stress. In tobacco leaves the mRNA levels of the constitutively expressed ribosomal protein gene Nt-L25 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 11 publications
3
97
0
4
Order By: Relevance
“…3B) was AtPP2A (At1g13320; Czechowski et al, 2005), and AtACT2 (At3g18780) was used for heat treatments (Figs. 3A and 8A;Volkov et al, 2003;Charng et al, 2007).…”
Section: Protoplast Two-hybrid and Gus Activity Assaysmentioning
confidence: 99%
“…3B) was AtPP2A (At1g13320; Czechowski et al, 2005), and AtACT2 (At3g18780) was used for heat treatments (Figs. 3A and 8A;Volkov et al, 2003;Charng et al, 2007).…”
Section: Protoplast Two-hybrid and Gus Activity Assaysmentioning
confidence: 99%
“…Relative AtBBM gene expression levels were determined using the comparative 2 ¡ CT method (Livak and Schmittgen2001). The expression level of the AtBBM gene in diVerent transgenic lines was normalized using the N. tabacum RIBOSOMAL L25 gene (GenBank accession L18908) as the reference (Volkov et al 2003) and the normalized AtBBM expression value from the transgenic line with the lowest AtBBM expression level as the calibrator.…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
“…It is generally assumed that housekeeping genes encoding proteins required for basal cell activities, such as central carbon metabolism, protein translation, cytoskeleton maintenance, and protein turnover, are expressed uniformly in different tissues and organs. However, it has been found that the expression of a number of such housekeeping genes, although constant in some experimental conditions, varies considerably in other cases (Volkov et al, 2003;Czechowski et al, 2005;Nicot et al, 2005;Remans et al, 2008). Therefore, their systematic use as reference genes may result in the misinterpretation of results.…”
mentioning
confidence: 99%